Environmental Taxes: Challenges and Opportunities for Sustainable Development - Ahmad Firdaus; Abdul Wahab; Lina Mariana; Munifa Munifa (Jurnal Riset Perpajakan: Amnesty, 2024)
This study explores the role of environmental taxes as a critical instrument for sustainable development, focusing on both the challenges and opportunities presented by their implementation in Indonesia. Environmental taxes, often termed "green taxes," are designed to mitigate environmental degradation by incentivizing industries to adopt eco-friendly practices and reduce their carbon footprint. Although Indonesia has made strides in incorporating environmental taxes through regulations like the carbon tax in Law No. 7 of 2021 and Government Regulation No. 46 of 2017, the application of these policies faces significant hurdles. Key challenges include limited public awareness and understanding of environmental taxes' benefits, as well as concerns over the financial impact on industries. Despite these obstacles, environmental taxes hold substantial potential for environmental enhancement by funding initiatives such as waste management, ecosystem restoration, and the promotion of renewable energy. This research emphasizes the importance of clear communication and collaboration among stakeholders to optimize the effectiveness of environmental tax policies, thereby contributing to Indonesia’s sustainable development goals.